The Effect of Vitamin C on Pathological Parameters and Survival Duration of Critically Ill Coronavirus Disease 2019 Patients: A Randomized Clinical Trial - Majidi, Nazanin; Rabbani, Faezeh; Gholami, Somayeh; Gholamalizadeh, Maryam; BourBour, Fatemeh; Rastgoo, Samira; Hajipour, Azadeh; Shadnoosh, Mahdi; Akbari, Mohammad Esmail; Bahar, Bojlul; Ashoori, Narjes; Alizadeh, Atiyeh; et al. (Frontiers in Immunology, 2021)
Introduction: Vitamin C has been reported to have beneficial effects on patients with COVID-19. This study aimed to investigate the effect of vitamin C supplementation on pathological parameters and survival duration of critically ill patients with COVID-19. Methods: This clinical trial was conducted on 120 hospitalized critical ill patients infected with COVID-19. The intervention group (n=31) received one capsule of 500 milligrams vitamin C daily for 14 days. The control group (n=69) received the same nutrition except vitamin C supplement. Measurement of pathological and biochemical parameters was performed at baseline and after two weeks of the intervention. Results: Following two weeks of vitamin C supplementation, the level of serum K was significantly lower in the patients compared with the control group (3.93 vs 4.21 mEq/L, P<0.01). Vitamin C supplementation resulted in a higher mean survival duration compared with the control group (8 vs 4 days, P<0.01). There was a linear association between the number of days of vitamin C intake and survival duration (B=1.66, P<0.001). The vitamin C supplementation had no effect on blood glucose, mean arterial pressure, arterial blood gas (ABG) parameters, Glasgow Coma Scale (GCS), kidney function, cell blood count (CBC), hemoglobin (Hb), platelet (Plt), the partial thromboplastin time (PTT), albumin, hematocrit (Hct), and other serum electrolytes including sodium (Na), calcium, and phosphorus (P). Conclusion: The present study demonstrated the potential of vitamin C supplementation in enhancing the survival duration of critically ill patients with COVID-19.